A Weighted Singular Trudinger-Moser Inequality (Journal of Partial Differential Equations, 2022)
In this paper, we obtained the extremal function for a weighted singular Trudinger-Moser inequality by  blow-up analysis in the Euclidean space $\mathbb{R}^2$. This extends recent results of Hou (J. Inequal. Appl.,  2018) and similar result was proved by Zhu (Sci. China Math., 2021).
Keywords: Singular Trudinger-Moser inequality; extremal function; blow-up analysis.